Institutional infrastructural preconditions and current perioperative anaesthesia practice in patients undergoing transfemoral transcatheter aortic valve implantation: a cross-sectional study in German heart centres. Issue 8 (4th August 2021) - Löser, Benjamin; Haas, Annika; Zitzmann, Amelie; Dankert, Andre; Treskatsch, Sascha; Reuter, Daniel A; Haas, Sebastian; Glass, Änne; Petzoldt, Martin
Abstract : Objectives: Transfemoral transcatheter aortic valve implantation (TF-TAVI) is an established therapy for patients with symptomatic aortic stenosis, which requires periprocedural anaesthesia care. In 2015, the German Federal Joint Committee released a directive on minimally invasive heart valve interventions which defines institutional infrastructural requirements in German heart centres. But still generally accepted expert consensus recommendations or national or international guidelines regarding periprocedural anaesthesia management for TF-TAVI are lacking. This nationwide cross-sectional study had two major objectives: first to assess the concordance with existing national regulations regarding infrastructural requirements and second to evaluate the status quo of periprocedural anaesthesia management for patients undergoing TF-TAVI in German heart centres. Design: Multicentre cross-sectional online study to evaluate the periprocedural anaesthesia management. Setting: In this nationwide cross-sectional study, electronic questionnaires were sent out to anaesthesia departments at TF-TAVI-performing centres in Germany in March 2019. Participants: 78 anaesthesia departments of German heart centres. Results: 54 (69.2%) centres returned the questionnaire of which 94.4% stated to hold regular Heart Team meetings, 75.9% to have ready-to-use heart-lung machines available on-site, 77.8% to have cardiac surgeons and 66.7% to have perfusionists routinely attending throughout TF-TAVI procedures. Regarding periprocedural anaesthesia management, 41 (75.9%) of the participating centres reported to predominantly use 'monitored anaesthesia care' and 13 (24.1%) to favour general anaesthesia. 49 (90.7%) centres stated to use institutional standard operating procedures for anaesthesia. Five-lead ECG, central venous lines, capnometry and intraprocedural echocardiography were reported to be routine measures in 85.2%, 83.3%, 77.8% and 51.9% of the surveyed heart centres. Conclusions: The concordance with national regulations, anaesthesia management and in-house standards for TF-TAVI vary broadly among German heart centres. According to the opinion of the authors, international expert consensus recommendations and/or guidelines would be helpful to standardise peri interventional anaesthesia care.